Autonomic dysfunction and fatigue in Parkinson’s disease: a report from Kenya - Imran Abuga; Juzar Oyungu; Jasmit Nyundo (Neurology Letters, 2023)
Fatigue is a common non-motor symptom of Parkinson's disease (PD) that significantly impacts patient quality of life. However, the underlying mechanisms of fatigue in PD remain unclear. The present study aims to investigate the involvement of autonomic dysfunction, specifically cardiac sympathetic denervation, in the pathogenesis of fatigue in PD. Thirty-two Caucasian PD patients with a well-defined follow-up period and no depression or cognitive impairment were included in the study. Fatigue was evaluated using the Parkinson Fatigue Scale-16 (PFS-16), and autonomic function was assessed through MIBG scintigraphy and comprehensive autonomic function tests (AFTs). The results showed that fatigue is a prevalent issue in PD, with a prevalence of 48.15%, and is positively correlated with disease duration and reduced parasympathetic activity as measured by the deep breathing test. However, no significant correlations were found between fatigue and other AFT parameters related to sympathetic innervation or noradrenergic pathway dysfunction as measured by MIBG myocardial scintigraphy. The findings suggest that fatigue in PD has a multifaceted pathophysiology and cannot be solely attributed to dysfunction in a single neurotransmitter system. The study highlights the importance of recognizing fatigue as a significant aspect of PD and further investigating its underlying mechanisms to improve patient care and management.